Communication—Electrochemical Behavior of UO22+ and Its Electrodeposition from UO2F2-FLiBe Melt. Issue 6 (1st April 2019) - Han, Dong; Li, Yuhe; Liu, Renduo; She, Changfeng; Huang, Wei; Gong, Yu; Li, Qingnuan
Abstract : To support the proposal for separating uranium from used fuel salt of Molten Salt Reactor (MSR), the electrochemical behavior of UO2 2+ in the carrier salt of MSR (LiF-BeF2, FLiBe) was investigated in this work. Cyclic voltammetry and square wave voltammetry measurements showed that the reduction of UO2 2+ in UO2 F2 -FLiBe melt with addition of KF exhibited one step with two exchanged electrons: UO2 2+ +2e − →UO2, with reduction peak of 1.93 V (vs . Be 2+ /Be). By potentiostatic electrolysis, the product of octahedral UO2 single crystals with micron size was obtained.